Implementation of the Surgi Mufti Dome Tourist Destination in View of DSN-MUI Fatwa No. 108/DSN-MUI/X/2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles - Razwa, Salma (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The tourism sector is one of the most important economic drivers in a region. The ulama through the Indonesian Ulema Council have made provisions in DSN-MUI Fatwa No. 108 of 2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles. In the city of Banjarmasin, people often make pilgrimage to the graves of ulama as a tourist destination. One of the tombs of popular scholars in Banjarmasin City is the Surgi Mufti Dome which still does not fully meet the criteria specified in the fatwa. Therefore, the author is interested in conducting research on how the implementation of the Surgi Mufti Dome is reviewed through DSN-MUI Fatwa No. 108 of 2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles. Keywords: Implementation, Tourist Destinations, DSN-MUI Fatwa Abstrak Sektor pariwisata merupakan salah satu penggerak ekonomi yang sangat penting di suatu daerah. Para ulama melalui Majelis Ulama Indonesia telah membuat ketentuan dalam Fatwa DSN-MUI No. 108 Tahun 2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah. Di kota Banjarmasin, masyarakat sering berziarah ke makam ulama sebagai tujuan wisata. Salah satu makam ulama yang populer di Kota Banjarmasin adalah Kubah Surgi Mufti yang masih belum sepenuhnya memenuhi kriteria yang telah ditentukan dalam fatwa tersebut. Oleh karena itu, penulis tertarik untuk melakukan penelitian tentang bagaimana implementasi Kubah Surgi Mufti ditinjau melalui Fatwa DSN-MUI No. 108 Tahun 2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah. Kata Kunci: Implementasi, Destinasi Wisata, Fatwa DSN-MUI